How do counsellors having menopausal symptoms experience their client work: An interpretative phenomenological analysis. Issue 4 (20th May 2019) - Bodza, Carol; Morrey, Tara; Hogan, Kevin F.
Abstract: Aim: The aim of this study was to discover whether menopausal symptoms have implications for counsellors in their therapeutic work. Method: Semi‐structured interviews were conducted with three counsellors who have experienced menopausal symptoms. The menopause is a unique experience for the individual. Interpretative phenomenological analysis therefore allowed for a detailed exploration of the participants' experiences. Findings: Four superordinate themes were identified: transitioning personal and professional identity during menopause; limited dialogue about the menopause; ethical dilemmas of practising as a counsellor when menopausal; and the influence of menopausal symptoms during client work. The findings demonstrated that participants each had very personal and individual experiences of the menopause. A lack of knowledge and understanding of the menopause and limited dialogue within society to discuss symptoms was also reflected in the counselling profession. The capacity to continue working therapeutically presented potential ethical dilemmas which were affected by menopausal symptoms. Conclusion: Counsellors' experiences of menopausal symptoms may create challenges in their therapeutic work, ranging from a mild distraction, a disconnection with a client, to having to cease engaging with client work. Implications for therapeutic practice are discussed.